Regression of liver fibrosis is progressive after sustained virological response to HCV therapy in patients with hepatitis C and HIV coinfection. Issue 12 (25th April 2013) - Casado, J. L.; Quereda, C.; Moreno, A.; Pérez‐Elías, M. J.; Martí‐Belda, P.; Moreno, S.
Summary: There are few data about the long‐term histological outcome of HIV‐/HCV‐coinfected patients after therapy with interferon and ribavirin. We performed an observational study of 216 patients who received therapy against HCV and who had at least three successive transient elastographies (TE) during the follow‐up. The primary endpoint was confirmed fibrosis regression, defined as a reduction of at least 1 point in Metavir fibrosis score, confirmed and without worsening in successive TE. At baseline, 23% had fibrosis stage 4 or cirrhosis. Overall, 82 (38%) achieved sustained virological response (SVR), without differences in baseline fibrosis or time of follow‐up. Confirmed fibrosis regression was observed in 55% of patients, higher for SVR (71% vs 44%; P < 0.01), and the likelihood of achieving fibrosis regression at 3, 5 and 7 years was 0.17, 0.51 and 0.67, respectively, for SVR patients, in comparison with 0.02, 0.23 and 0.41 for no SVR patients ( P < 0.01, log‐rank test at any time point). Progressive regression, defined as continuous improvement in successive TE, was observed in 62% of patients with advanced liver fibrosis or cirrhosis who achieved SVR. In a Cox regression model, only SVR (HR, 4.01; 95% CI, 2.33–7.57; P < 0.01) and a younger age (HR, 1.14; 95% CI, 1.05–1.25; P < 0.01; per year) were associated with fibrosis regression. This study confirms that the rate of liver fibrosis regression increases during the follow‐up after SVR to interferon therapy in HIV‐/HCV‐coinfected patients.